Entre disputas e debates: a construção da BNCC de História - Juzwiak, Victor Ridel (2021)
The process of elaborating the National Common Curricular Base was complex and took place amid political and epistemological disputes. The Base has been foreseen since the Federal Constitution of 1988 and during that period other experiences of common curriculum policies were developed in the country. However, BNCC only takes place after twenty-nine years. During this period, several laws, guidelines and plans were created and currently legally support the BNCC document. The curriculum component of History has been the subject of several controversies throughout the document construction process. The Brazilian political scenario had an important impact during the process of producing the document. Between 2015 and 2017, three versions of the BNCC were elaborated, published, and released for public consultation. In this sense, the general objective of this research is to understand the process of technical, political and epistemological construction of the BNCC of History for the elementary school from its versions and the specialists who wrote it. For this, two methodological instruments were used for data production. Documentary analysis was used to understand the laws that underpin the BNCC and to analyze the epistemological and ideological differences of the three versions of the BNCC in History. The use of interviews for the production of narratives allowed knowing the process of elaboration and construction of the document from the experiences of the specialist researchers who made up the commissions. Thus, the research shows that the versions of the BNCC present proposals with differences and similarities. The differences point to political, ideological, methodological and epistemological conceptions that served to guide the production of documents. Knowing and understanding these concepts are fundamental to the teaching and learning process, as they allow a critical look at the curriculum proposal of BNCC. The similarities of the three versions are present in the way the proposed contents are organized, that is, based on competences and abilities. Following the models of national exams.